Leveraging online social networks for effective collaborative learning - A students' perspective - Firdhous, Mohamed; Junriana, ,; Budiman, Shahril; Matridi, Raja Abumanshur; Aziz, Mohd Amar; Sharif, Iza'an Shazwan; Ayob, Noor Hadzlida (2013)
Online social networks have become very popular in recent times.Online social networks have transformed the Internet from information gathering and dissemination medium to a collaborative environment.Currently the number of registered online social network users exceeds one billion and they access these sites for various reasons including to form communities, to produce and consume media content in revolutionary ways.There is common perception among adults that youngsters spend more time on social media than on studies or other useful work.According to the surveys carried out by the leading research institutes, more than half of the online social network users are between 20 and 40 years of age and many users have personal profiles on more than one social network sites.The distribution of registered users between different online social networks vary vastly with Facebook taking the largest share at 92% followed by MySpace at 29%, Linkedln at 18% and Twitter at 13%.Among college students, Facebook is still the most commonly visited social network site at 88.5% followed by Twitter at 11.5%. College students access social network sites for various reasons with communication with friends and family being the dominant one.Several researchers have been carried out how the social network can be used to improve teaching and learning environments.But most of these researchers have been confined to helping adult learners or improving teaching environments.In this research, it has been proposed to study how social networks can be leveraged for effective col1aborative learning where the students use the social media as the main communication tool.It has also been proposed to study what factors would encourage college students to use social media for collaboration in their studies.As part of the research, a detailed questionnaire will be administered among college students both at undergraduate and postgraduate levels covering a wider demography including males, females, employed, unemployed, full time and part time students. Finally both descriptive and exploratory analysis will be carried out on the data collected.